إيذاء النساء باثولوجيا التحرّش الجنسي الالكتروني بالمرأة - أحمد الديب, هدى; محمد سليمان, محمود عبد العليم (Changement Social, 2018)
تحاول هذه الورقة تناول ظاهرة حديثة في المجتمعات هي ظاهرة التحرش الإلكتروني بهدف تحديد ماهيتها وأنماطها وأثارها وكيفية مواجهتها. وكان الدافع الرئيس لبحث ومقاربة هذه الظاهرة هو ما تعانيه الكثيرات من مستخدمات شبكة الإنترنت من تعرّضهن لأشكال مختلفة من المضايقات، بدءًا من الإلحاح بالتعارف من أشخاص لا يعرفونهم، أو تعرّضهن للملاحقة والتعقّب من جانب آخرين ممن لديهم خلافات شخصية معهن. أو رسائل تحتوي على العبارات التي تجاوزت حد المعاكسة أو محاولات التعارف واتجهت أحيانًا إلى عرض صور جنسية وأرقام تليفونات وعناوين كعروض لممارسة الجنس بشكل صريح. وفي نهاية الورقة عرض بعض الآليات، واقتراح  بعض الخطوات التي يمكن من خلالها مواجهة التحرش الإلكتروني. This paper attempts to address the phenomenon of modern societies that is the phenomenon of electronic Harassment With a view to determining their nature, patterns, effects and how to confront them. The main motivation to discuss and approach this phenomenon is the suffering of many Internet users from exposure to various forms of Harassment, From the urgency of getting to know people they do not know or being persecuted and pursued by others who have personal differences with them. Or messages that contain phrases that have exceeded the opposite limit or attempts at dating and have sometimes tended to display sexual images, phone numbers, and addresses as explicit sex offers. At the end of the paper, some mechanisms were presented, and some steps were suggested in order to confront electronic harassment